Levels of Nursing Ethics Knowledge among Students without Clinical Experience - Panyuwa, Ayu Afriani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Nursing ethics plays a crucial role in shaping the nursing profession, and a thorough understanding of ethical values serves as the foundation for delivering quality healthcare services. Objective: To describe the level of nursing ethics knowledge among nursing students who do not yet have clinical practice experience in hospitals. Method: This research employed a quantitative descriptive research design. Data analysis utilized a descriptive statistical approach, presenting frequency data and percentage levels of knowledge. The population in the study consists of all first-semester nursing students who have yet to undergo clinical practice. The sampling technique employed is purposive sampling. The research sample comprised 82 students lacking clinical practice experience. The questionnaire assessing nursing ethics knowledge underwent validity testing, obtaining a value of 1 > 0.355 and reliability testing with a Cronbach's alpha value of 0.961 > 0.60. The questionnaire consisted of 29 items. Results: The findings of this study indicate percentage categories for the level of nursing ethics knowledge among students as follows: (21%) abysmal, (28%) poor, (20%) fair, (18%) good, and (16%) very good. Conclusions: Innovative learning strategies, practical experiences, and in-depth curriculum studies in the field of professional ethics in nursing are important to help address the limitations of nursing ethics knowledge.